Cardiofaciocutaneous syndrome and immunodeficiency: data from an international multicenter cohort - Di Majo, Benedetta Elena; Leoni, Chiara; Cartisano, Eleonora; Fossati, Chiara; Viscogliosi, Germana; Trevisan, Valentina; Bruno, Lucia Pia; Conti, Francesca; Moratti, Mattia; Monaco, Emilia; Rigante, Donato; Rivalta, Beatrice; et al. (Frontiers in Immunology, 2025)
IntroductionCardiofaciocutaneous syndrome (CFCS) is a rare syndromic disorder caused by germline mutations affecting the RAS/MAPK pathway. It is characterized by distinctive craniofacial dysmorphism, congenital heart defects, skin abnormalities, gastrointestinal dysfunction, neurocognitive impairment, and epilepsy. Emerging evidence suggests an association with hypogammaglobulinemia, but a comprehensive characterization of immunological abnormalities in CFCS is lacking.MethodsWe conducted a retrospective, multicenter observational study to investigate the immunological phenotype of CFCS. Clinical features, immune-related manifestations, and laboratory parameters were analyzed to delineate the immunological profile of affected individuals.ResultsA total of 56 patients with a confirmed clinical and molecular diagnosis of CFCS were included, with a median age at evaluation of 13 years (range: 1–39 years). Increased susceptibility to infections was reported in 18/56 patients (32%), while autoimmune manifestations were observed in 14/56 patients (25%). Common immunological findings included monocytosis (32%), lymphopenia (21%), and hypogammaglobulinemia, with decreased IgG, IgA, or IgM levels in 21%, 40%, and 35% of patients, respectively. Genotype-phenotype analysis revealed that BRAF mutations were predominantly associated with T-cell lymphopenia, whereas MAP2K1 mutations were linked to monocytosis, reduced naïve and switched-memory B cells, and hypogammaglobulinemia. Immunodeficiency-related treatments, including immunoglobulin replacement therapy, antibiotic prophylaxis, or immunosuppressive therapy, were administered to 6/56 patients (11%).ConclusionsCFCS is associated with recurrent yet heterogeneous immunological abnormalities, including lymphopenia, hypogammaglobulinemia, and increased infection susceptibility. Given these findings, routine immunological assessment should be considered in CFCS patients to facilitate early detection and appropriate management of immune dysfunction.